Formação e (re)socialização de adolescentes em privação de liberdade: práticas e políticas educacionais no centro socioeducativo de Unaí – CSEUN - (:unkn) unknown (Universidade Federal de Goiás, 2018)
This research starts attempting to analyze the formation and resocialization process of adolescents in conflict with the law, that comply with the socio-educational measure of internment, provided for in the article 121 of Law 8.069 / 90 - of teenager - ECA (BRASIL, 2016), under the perception of the adolescents, who literally live the stigmas of this system, in the Socio - Educational Center of Unaí - MG. The specific objectives consists in examine the educational policies that institutionalized and assist that unit; investigate the educational practices developed in the local, specifically in the school, and how the adolescentes articulate with the educational policies turned on the formation and resocialization of adolescents and their needs, and finally, understand the socio-educational profile of these subjects, checking their perception in relation to the Socio- educational System, about their process of formation and resocialization and the life projects constructed while they are deprived of their liberty. The identification of the tools that make up all educational policies and practices and the grade of commitment about the implementation of the entire pedagogical, socio-educational and socializing project that is extremely important in order to establish specific strategies to help them in the adequate management of the resocialization program by the Education, acting not "through deprivation of liberty" but, "despite it." Thus, it is evident that the accomplishment of this research includes both the legal dimension - of the Law, as well as the pedagogical dimension - of Education. This research in education is qualitative approach. Observation, semi-structured interviews and questionnaires were used as data collect instruments to measure the desired results through the presented objectives The questionnaires were applied to teachers and adolescents, the interview was made only with them. In general terms, it was possible to conclude that the adolescents believe that the educational practices, contribute to their formation and the place is propitious to reflections that favor changes in the way of thinking and acting, contributing in the elaboration of plans and life projects.
Formation and (re) socialization of adolescents in deprivation of liberty: practices and educational policies in the socio-educational center of Unaí - CSEUN
Keywords: Formação; Adolescente; (Re)socialização; Medidas socioeducativas; Formation; Resocialization; Adolescents; Socio-educational measures; CIENCIAS HUMANAS::EDUCACAO